1981
DOI: 10.1103/physrevb.24.730
|View full text |Cite
|
Sign up to set email alerts
|

Lattice dynamics of hcp Hf

Abstract: Inelastic neutron scattering techniques have been used to study the lattice dynamics of hcp Hf. The phonon dispersion curves along the [001], [100], and [110]symmetry directions were determined at 295 and 1300 K, and a selected number of phonon frequencies were measured also at 800 K. As the temperature decreases we observe a rather large increase in the frequencies of all but the [001] LO branch. The zone-center mode of the [001] LO branch, on the other hand, softens appreciably, and at room temperature this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…We have also examined the splitting of the bands in terms of atom localization, and found that both bands are equally localized on the two atoms in the hcp unit cell in all cases. 4 [11,12]. The most striking feature of the calculated phonon frequencies is the anomalously low values for Tc and Re, especially when compared to those obtained for Ru and Os.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…We have also examined the splitting of the bands in terms of atom localization, and found that both bands are equally localized on the two atoms in the hcp unit cell in all cases. 4 [11,12]. The most striking feature of the calculated phonon frequencies is the anomalously low values for Tc and Re, especially when compared to those obtained for Ru and Os.…”
Section: Resultsmentioning
confidence: 71%
“…the [001] longitudinal optical phonon excitations. It has been known for a long time that in Tc and Re, and to a somewhat less extent in Zr and Hf as well, the [001] longitudinal optical phonon branches have anomalously low frequency and show anomalous temperature dependence [11,12]. The origin of these anomalies was ascribed to the electronic bands near the Fermi level [10].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In fact, the E 2g optical phonon mode and the coupled elastic shear modulus C 44 were experimentally found to show an anomalous pressure-dependent behavior [19], but up to now this issue has not been clarified yet. It was also reported that the lattice distortion will shift the degeneracy of the bands in the A-H-L plane, and for the bands close to the Fermi level this splitting will reduce the electronic energy and a phonon anomaly will occur [20]. Despite the anomalous behavior mentioned in the studies above, no clear theoretical clues have been provided, i.e., the relation between mechanism and phenomena is still not established.…”
Section: Introductionmentioning
confidence: 85%
“…The phonon dispersion curves for α-Hf under pressure from 0 GPa (black curves), 10 GPa (blue curves), 15 GPa (green curves), to 40 GPa (red curves) respectively. The pink stars present the experimental data measured by neutron spectroscopy at 295 K [20].The red arrow points out the E 2g mode in the phonon spectra.…”
Section: A Structural Elastic and Vibrational Propertiesmentioning
confidence: 99%